Treatment of a severe dental lateral luxation associated with extrusion in an 8-month-old baby: a conservative approach - Cunha, Robson Frederico [UNESP]; Delbem, ACB; Vieira, AED; Pugliesi, DMC (Blackwell Munksgaard, 2005)
This case report documents the trauma and follow-up care of lateral luxation associated with extrusion of the lower central incisors in an 8-month-old patient. The teeth were repositioned by digital pressure and stabilized using proximal sutures. Clinical and radiographic follow-up 40 months after the injury showed alterations in both incisors, but both remained functional and free of pathology.
Keywords: dental injuries; trauma; primary teeth; luxation injuries